(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article presents the accounts of the pedagogic experience with drama workshops held with inmates of Papuda (DF) Prison System (located in Brazil’s capital, Brasilia) between 2005 and 2013. As a result of this work, the book “Teatro em Cadeado - uma experiência em cela de aula, 2019” was written and published. This publication contains experiences with the male and female prison systems and their particularities. The appropriation of the performing language with people deprived of freedom is a psychosocial challenge. By proposing free expression in an oppressor space, the practice of drama has many functions, which is not only the artistic expression, it is the deconstruction of a marginalized and oppressed identity. The exercise of this artistic language amazed the students/inmates when they found themselves capable of transforming their pessimist reality, looking at themselves in a new way, and leading a transforming and liberating future